Patent Granting on Marine DNA Discovery (Medico Legal Update, 2021)
In recent years, the world has experienced various medical treatments originates from the ocean, such ascytarabine, vidarabine, and ziconotide. Marine represents a great source of species with potential medicaltreatments due to these species’ unique properties; however, the research and discovery of this industrydemand high financial resources and time management. Hence, the international government has employedintellectual property rights and patent granting as a mechanism to promote innovative research. This paperexplores the benefits and disadvantages of patent granting on marine DNA discovery and application.